Remote Ischemic Preconditioning and Contrast-Induced Acute Kidney Injury in Patients Undergoing Elective Percutaneous Coronary Intervention: A Randomized Clinical Trial - Karolina Stokfisz, MD; Anna Ledakowicz-Polak, MD, PhD; Michal Kidawa, MD, PhD; Marzenna Zielinska, MD, PhD (Elsevier, 2020)
Background: Contrast-induced acute kidney injury (CI-AKI) is a common cause of hospital-acquired AKI and a serious complication of percutaneous coronary intervention. Objective: The aim of the present study was to assess whether remote ischemic preconditioning (RIPC) reduces the incidence of CI-AKI. Methods: We conducted a prospective, randomized, sham-controlled clinical study. The study included 101 patients admitted to the Intensive Cardiac Therapy Clinic of Medical University of Lodz for elective percutaneous coronary intervention. The participants were randomly assigned in a 1:1 ratio to either a control group (n = 51) or an RIPC group (n = 50). In the latter, RIPC was achieved before percutaneous coronary intervention by 4 cycles of 5-minute inflation of a cuff on the left upper arm to 200 mm Hg followed by 5-minute deflation. In the control group, a deflated cuff was placed on the left arm for 40 minutes. Serum creatinine concentration was measured to check for the presence of CI-AKI within 48 to 72 hours of percutaneous coronary intervention. Serum neutrophil gelatinase-associated lipocalin level was also measured within 3 hours. Results: CI-AKI occurred in 2 patients from the RIPC group (4%) and 3 patients from the control group (5.9%), but the difference was not significant (P = 0.98). The patients who developed CI-AKI also demonstrated increased serum neutrophil gelatinase-associated lipocalin concentrations (the area under the receiver operator characteristic curve = 0.97; 95% CI, 0.938-1.00; P < 0.00) and the optimal cutoff point value was 118.9 ng/mL. Conclusions: The use of RIPC before elective percutaneous coronary intervention was not found to prevent CI-AKI. ClinicalTrials.gov identifier: NCT03761368. (Curr Ther Res Clin Exp. 2020; 81:XXX-XXX)